# Math

posted by
**Gina**
.

^=exponents

/= divide

So I am not sure how to do this. It is an example in my book but I still don't get it. Can you work through ti so I can do my real work.

(-1^2+-1^-2)^-1

(-1^2+-1^-2)^-1 =

First, do work within the parentheses.

-1*-1 = 1 and -1^{-2} = 1/(-1^{2}) =

[1+(1/(-1^{2})]= [1 + 1/1]^{-1 }. (One moves the negative exponent in the numerator by making it 1/(the positive exponent; thus, -1^{-2} becomes 1/(-1)^{2}.

Now flip the -1 exponent by taking the reciprocal.

[1/(1+1}] = 1/2

<Check my thinking. Check my arithmetic. There are so many exponents and negative exponents that it is easy to make a mistake. Furthermore, when I try to do the exponents it is easy to forget to turn the exponents off. I hope this turns out ok.

It looks ok but check my work anyway.